THE IMPLEMENTATION OF PARENTAL INVOLVEMENT IN SUPPORTING THE STUDENTS' ENGLISH LITERACY ACHIEVEMENT OF THE FOURTH GRADE STUDENTS AT NBBS SINGARAJA - ., Ni Putu Ayu Surya Utari Dewi; ., Dra. Luh Putu Artini, MA., Ph.D.; ., Luh Diah Surya Adnyani, S.Pd. (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
Penelitian ini bertujuan untuk menganalisis penerapan keterlibatan orangtua dalam mendukung prestasi literasi bahasa Inggris siswa di NBBS Singaraja dan faktor yang mendukung suksesnya penerapan keterlibatan orangtua tersebut. Analisis keterlibatan orangtua dalam penelitian ini didasari oleh enam kerangka keterlibatan orangtua oleh Epstein (2009). Penelitian ini menggunakan model penelitian deskriptif kualitatif dengan subyek penelitian yaitu siswa kelas IV di North Bali Bilingual School (NBBS) Singaraja, sementara obyek penelitian ini adalah keterlibatan orangtua yang diterapkan melalui program-program sekolah untuk mendukung prestasi literasi bahasa Inggris siswa di NBBS Singaraja. Data dikumpulkan dengan metode wawancara dan analisis dokumen. Berdasarkan hasil analisis data ditemukan bahwa: (1) keterlibatan orangtua di NBBS diterapkan melalui beberapa strategi yaitu melalui perseorangan (konseling dan parent’s conference) dan pertemuan (English Day Camp). Beberapa usaha juga dilakukan sekolah untuk melibatkan orangtua dalam mendukung literasi siswa yaitu dengan adanya Book Week, Memo Book, Class News, Reading Log Book dan Studi Lapangan. (2) faktor yang mempengaruhi suksesnya penerapan keterlibatan orangtua dalam mendukung prestasi literasi bahasa Inggris siswa di NBBS Singaraja adalah konsistensi orangtua dalam mengikuti sistem/aturan sekolah sehingga terbentuk suatu kebiasaan bagi siswa. Kata Kunci : Keterlibatan Orangtua, Literasi Bahasa Inggris, Prestasi Literasi Bahasa Inggris Siswa. This study aimed at analyzing the implementation of parental involvement in supporting the students’ English literacy achievement of the fourth grade students at NBBS Singaraja and factors that support the success of the implementation of parental involvement in supporting the students’ English literacy achievement at NBBS Singaraja. Parental involvement activities in this study was analyzed based on Epstein’s six types of parental involvement framework (2009). This study used a descriptive qualitative research design by involving the fourth grade students at NBBS Singaraja. The object of this study was parental involvement which is practiced through the school’s programs. The data were collected by conducting an interview and document analysis. Based on the result of the data analysis, it was found that (1) parental involvement in NBBS is practiced through many strategies like in person (counseling and parents’ conference) and in gathering (English Day Camp). Some efforts were also done to get parents involved in their children’s literacy activities through the existence of Book Week event, Memo book, Memo Book, Class News, Reading Log Book, and Field Study. (2) Factor that supports the success of the implementation of parental involvement in supporting the students’ English literacy achievement at NBBS Singaraja was the parents’ consistency in following the school’s system, so that the students’ habit can be built. keyword : Parental Involvement, English Literacy, Students’ English Literacy Achievement.